Effect of CdSeS/ZnS quantum dot concentration on the electro-optical and dielectric properties of polymer stabilized liquid crystal - Kocakulah, Gulsum; Algul, Gulay; Koysal, Oguz (Elsevier, 2020)
Our research paper has been discussed electro-optical and dielectric characterization of polymer stabilized liquid crystal (PSLC) and its doped form with different concentration of CdSeS/ZnS quantum dot (QD). PSLC composite was prepared using a nematic liquid crystal (E63) and Poly(methyl methacrylate) (PMMA) polymer. In order to improve physical properties, composites were dispersed with different concentration of CdSeS/ZnS QD. The electro-optical and dielectric properties of the composites were investigated depending on the frequency and voltage. Considerable physical parameters such as threshold voltage, dielectric anisotropy, relaxation frequency and response time were obtained from the experimental data. The results show that QD contribution and polymer networks change the electro-optical and dielectric properties of PSLC and these can become a focus of interest for new applications of PSLC composites in the future. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Polymer stabilized liquid crystal; Quantum dot; Polymer network; Dielectric properties